Professional burnout in nurses working in the primary health care - Dębska, Grażyna; Cepuch, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. The burnout syndrome is characteristic for professions aiming at helping other people. Nursing is one of them. Aim: The analysis of some conditions determining the professional burnout syndrome in nurses working in the primary health care i.e. sense of lack of achievements, emotional exhaustion, depersonalization, methods of managing stress, life changes burden, crisis concerning valuation. Material and methods: The study was performed among 35 nurses working in the primary health care (age x = 37.2 ± 6.3); 74.2% of participants lived in rural area. The following measures were used in order to analyze conditions determining burnout; the Maslach Burnout Inventory MBI, Social Responsiveness Scale (SRS.T), The Questionnaire of life changes (KKZ) and KKW Conclusions: 1. The study group didn’t experience burnout for their members presented relatively high level of selfvalue in their work, moderate level of emotional exhaustion and low level of depersonalization. 2. Participants usually applied constructive strategies in stressful situations. 3. Social support plays an important role in sustaining nurse’s self-esteem. 4. Constant education was one of the methods increasing self-esteem in the studied group. 5. High level of emotional exhaustion may result from life changes burden.